Paradigma Pemidanaan di Indonesia (Kajian Keadilan Restoratif) - Brilian Capera (Universitas Islam Indonesia, 2021)
This study aims to examine restorative justice as a paradigm of punishment in Indonesia. This is a normative legal research that uses statutory and conceptual approaches. The results of this study indicate that the criminal system in force in Indonesia is still based on the repressive paradigm of retributive justice, so that imprisonment is the most frequent punishment imposed on perpetrators of criminal acts. To be able to achieve the expected sentencing objectives, namely to fulfill the rights of the parties, it is important to build a paradigm of punishment based on restorative justice through changes in legal substance, legal structure, and legal culture so that the effectiveness of criminal law enforcement can be realized.Keywords: Paradigm; penal system; restorative justiceAbstrakPenelitian ini bertujuan untuk mengetahui kajian atas keadilan restoratif sebagai paradigma pemidanaan di Indonesia. Penelitian ini merupakan penelitian hukum normatif yang menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian ini menyimpulkan bahwa sistem pemidanaan yang berlaku di Indonesia masih berdasar pada paradigma keadilan retributif yang sifatnya represif, sehingga pidana penjara menjadi pidana yang paling sering dikenakan kepada pelaku perbuatan pidana. Untuk dapat mencapai tujuan pemidanaan yang diharapkan yaitu memenuhi hak-hak para pihak, penting untuk membangun paradigma pemidanaan berbasis keadilan keadilan restoratif melalui perubahan substansi hukum, struktur hukum, dan budaya hukum sehingga dapat terwujud efektivitas penegakkan hukum pidana.Kata Kunci: Keadilan restoratif; paradigma; sistem pemidanaan